2015
DOI: 10.1104/pp.15.00432
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulating the Expression of 53 Soybean Transcription Factor Genes Uncovers a Role for SPEECHLESS in Initiating Stomatal Cell Lineages during Embryo Development  

Abstract: We used an RNA interference screen to assay the function of 53 transcription factor messenger RNAs (mRNAs) that accumulate specifically within soybean (Glycine max) seed regions, subregions, and tissues during development. We show that basic helix-loophelix (bHLH) transcription factor genes represented by Glyma04g41710 and its paralogs are required for the formation of stoma in leaves and stomatal precursor complexes in mature embryo cotyledons. Phylogenetic analysis indicates that these bHLH transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 56 publications
0
22
0
1
Order By: Relevance
“…Glyma.05G189400, homologous to AtTSK, is required for cell cycle progression (Suzuki et al 2005). Glyma.04G238400 and Glyma.06G125500, homologous to AtSPCH, initiate asymmetric cell divisions in leaves and are essential for stomatal development (Danzer et al 2015). AtCHR17, AtDDM1, AtTSK, and AtSPCH are all repressed in leaves in T7.…”
Section: Snp Identification From Resistant and Susceptible Genotypesmentioning
confidence: 99%
“…Glyma.05G189400, homologous to AtTSK, is required for cell cycle progression (Suzuki et al 2005). Glyma.04G238400 and Glyma.06G125500, homologous to AtSPCH, initiate asymmetric cell divisions in leaves and are essential for stomatal development (Danzer et al 2015). AtCHR17, AtDDM1, AtTSK, and AtSPCH are all repressed in leaves in T7.…”
Section: Snp Identification From Resistant and Susceptible Genotypesmentioning
confidence: 99%
“…Overexpression of aquaporin in tomatoes (Sade et al, 2010) and grapevines (Perrone et al, 2012) increased WUE under both optimal and water stress conditions. For stomatal development, it was shown that bHLHs are required for the development of soybean stomata, revealing the relationship between the accumulation sequence of GmSMFs and the initial growth stage of mature GCs (Danzer et al, 2015). Despite the success in breeding drought tolerant crops, most horticultural crops and cash crops are eudicots that do not have stomata similar to those in the crops of the grass family.…”
Section: Breeding Crops With Highly Water Use Efficient Stomatamentioning
confidence: 99%
“…Stomatal lineage pausing takes place in various natural contexts, either developmentally programmed (as in soybean (Glycine max) seed cotyledons; Danzer et al, 2015) or in response to environmental cues (such as osmotic stress; Skirycz et al, 2011), or both (as described for A. thaliana seedlings kept in the dark; Kang et al, 2009). These findings suggest that stomatal lineage initiation (the still poorly understood selection of MMCs from the protoderm and their first asymmetric divisions) occurs easily, perhaps under a permissive or even a default programme, and that it does not seem to require TMM because it takes place in tmm mutants.…”
Section: The Complexity Of Tmm-associated Functionsmentioning
confidence: 99%